2003
DOI: 10.1042/bj20020835
|View full text |Cite
|
Sign up to set email alerts
|

Triadimefon, a fungicidal triazole-type P450 inhibitor, induces brassinosteroid deficiency-like phenotypes in plants and binds to DWF4 protein in the brassinosteroid biosynthesis pathway

Abstract: Triadimefon (Bayleton), a widely used triazole-type fungicide, affects gibberellin (GA) biosynthesis and 14 alpha-demethylase in sterol biosynthesis. The present study revealed that the phenotype of Arabidopsis treated with triadimefon resembled that of a brassinosteroid (BR)-biosynthesis mutant, and that the phenotype was rescued by brassinolide (BL), the most active BR, partly rescued by GA, and fully rescued by the co-application of BL and GA, suggesting that triadimefon affects both BR and GA biosynthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…To compare the potency of the identified compounds in affecting plant growth we decided to analyze their ability to inhibit hypocotyl elongation of cress, an assay frequently used to investigate BR action [21], [22], [35], [24], [36]. As shown in Figure 2B, voriconazole strongly reduced hypocotyl elongation of cress with significant effects detectable at a concentration of 30 nM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the potency of the identified compounds in affecting plant growth we decided to analyze their ability to inhibit hypocotyl elongation of cress, an assay frequently used to investigate BR action [21], [22], [35], [24], [36]. As shown in Figure 2B, voriconazole strongly reduced hypocotyl elongation of cress with significant effects detectable at a concentration of 30 nM.…”
Section: Resultsmentioning
confidence: 99%
“…However, their activities vary as they interfere with the biosynthesis of different metabolites important for plant development including BRs, gibberellins (GAs) and sterols, respectively [28], [39], [21], [22], [24], [36].…”
Section: Resultsmentioning
confidence: 99%
“…Plants treated with 1 mM triadimefon, which inhibits biosynthesis of brassinosteroids and gibberellins (Buchenauer and Rohner, 1981;Asami et al, 2003), showed a small reduction in the number of stomata, with the exception of Col-0 (Table 1). This reduction was counteracted by the co-application of 0.5 mM epibrassinolide, confirming that this plant regulator promotes stomata formation in the hypocotyl (Table 1).…”
Section: Brassinosteroids Promote Stomatal Formation In the Hypocotylmentioning
confidence: 99%
“…The triazole-type BR biosynthesis inhibitor, brassinazole, inhibits the BR C-22 hydroxylation step by binding to CYP90B1 protein (Asami et al 2001). Also the widely used triazole-type fungicide, Triadimefon, binds to CYP90B1 to suppress BR biosynthesis (Asami et al 2003). In rice CYP90B2 mutants exhibit a weak phneotype due to the presence of CYP724B1 that can also catalyse C-22 hydroxylation as described below (Sakamoto et al 2006).…”
Section: Cyp90bmentioning
confidence: 96%